An Exploratory Investigation on the Challenges to the New Brazilian Automotive Suppliers - Pereira, Giancarlo Medeiros; Geiger, Albert (Brazilian Journal of Operations & Production Management, 2010)
This paper analyzes the B2B (business-to-business) relationships between big and small or medium-sized enterprises in the automotive sector in Brazil to tentatively identify the challenges that hinder the insertion of SMEs (small and medium-sized nterprises) in this supply chain. This multiple case study analyzed the largest car part manufacturers and the largest car assembly plants located in the state of Rio Grande do Sul, Brazil. This was followed by studies of small and medium-sized businesses that had been indicated by the executives of the large companies studied. The objective was to answer the question: why are very few SMEs successful in their attempts at inserting themselves in the automotive supply chain. As identified, the main challenges faced by SMEs that do not operate in the auto chain are: the differences in the organizational objectives and the little know-how about the reality of B2B transactions in this sector.